2019
DOI: 10.1089/biores.2019.0026
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Drug Permeability Using In Vitro Blood–Brain Barrier Models with Human Induced Pluripotent Stem Cell-Derived Brain Microvascular Endothelial Cells

Abstract: The strong barrier function of the blood–brain barrier (BBB) protects the central nervous system (CNS) from xenobiotic substances, while the expression of selective transporters controls the transportation of nutrients between the blood and brain. As a result, the delivery of drugs to the CNS and prediction of the ability of specific drugs to penetrate the BBB can be difficult. Although in vivo pharmacokinetic analysis using rodents is a commonly used method for predicting human BBB permeability, novel in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…For instance, permeability of drugs and nutrients across a monolayer of hPSC-derived BMEC-like cells correlated with in vivo rodent brain transport rates [1], and subsequently, PET radioligand transport across BMEC-like cells correlated with human BBB permeability [16]. It has also been demonstrated that these cells can be used to compare the relative in vitro BBB permeability of known drugs, to evaluate the permeability and efflux profile of experimental drugs, and to explore the mechanisms of nutrient transport [1,[11][12][13][14][15][16]. hPSCderived models can also be used to compare transport of antibodies across the BBB to identify antibody-and species-dependent effects on trans-BBB transport [7,19] and identify new antibodies capable of binding the human BBB [31].…”
Section: Main Textmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, permeability of drugs and nutrients across a monolayer of hPSC-derived BMEC-like cells correlated with in vivo rodent brain transport rates [1], and subsequently, PET radioligand transport across BMEC-like cells correlated with human BBB permeability [16]. It has also been demonstrated that these cells can be used to compare the relative in vitro BBB permeability of known drugs, to evaluate the permeability and efflux profile of experimental drugs, and to explore the mechanisms of nutrient transport [1,[11][12][13][14][15][16]. hPSCderived models can also be used to compare transport of antibodies across the BBB to identify antibody-and species-dependent effects on trans-BBB transport [7,19] and identify new antibodies capable of binding the human BBB [31].…”
Section: Main Textmentioning
confidence: 98%
“…We defined this cell type as hPSC-derived BMECs. The resultant cells have proven useful for examining interactions between cells of the neurovascular unit [1][2][3][4][5][6][7][8][9][10], evaluating experimental drug permeability at the BBB [1,[11][12][13][14][15][16], and modeling human genetic disease using hiPSCs derived from patient sources [9,10,13], among other applications.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the species-specific differences in transporter and efflux pump expression, human iPSC-based BBB models are an attractive platform to test drug permeability. These models more accurately predict human BBB permeability compared to non-human BBB models [69] and hold great promise in providing a high-throughput platform for predicting human CNS drug permeabilities and circumventing the need for animal-based testing [70]. Early iPSC-derived BBB models highlighted the ability of iBMECs to correlate well with in vivo drug permeability using transwell systems [12,71] and subsequent studies have expanded permeability testing to microfluidic platforms under fluid flow that more closely mimic in vivo conditions [19,31,64].…”
Section: Drug Transport and Deliverymentioning
confidence: 99%
“…by increasing flow through the collateral circulation ‘bypassing’ the occluded vessel). However, within areas of injury, there can be vasoconstriction that can cause capillary occlusion even after reperfusion (no-reflow phenomenon) regulated by pericytes [ 147 ]. In addition, there are cytotoxic effects on BECs with mitochondrial dysfunction and altered ion channel and transporter activity (e.g.…”
Section: Modeling the Bbb Pathology Of Cerebrovascular Diseasementioning
confidence: 99%